All clinical stressors are not created equal: Differential task stress in a simulated clinical environment. Issue 2 (15th March 2022) - Joseph, Melissa; Ray, Jessica M.; Chang, Jungsoo; Cramer, Laura D.; Bonz, James W.; Yang, Thomas J.; Wong, Ambrose H.; Auerbach, Marc A.; Evans, Leigh V.
Abstract: Background: A variety of stressors are encountered while working in the emergency department and are often recreated in simulation‐based medical education. We seek to examine the physiologic and stress state response of participants in a simulated clinical environment to commonly encountered stressors. Methods: Emergency medicine (EM) residents participated in a randomized, controlled trial of six simulated patient encounters with one of three stressors, medical difficulty, interpersonal challenge, and technology/equipment failure, randomized into each scenario. Participants wore smart shirts to measure heart rate variability (HRV) at rest and just after the introduced stressor and completed the Short Stress State Questionnaire (SSSQ) before and after each scenario. Results: Twenty‐seven EM residents participated in the study. Interpersonal challenge resulted in increased distress as measured by SSSQ compared to the other two stressors (one way ANOVA, F[2, 144] = 9.95, p  < 0.001). There was no difference in worry or task engagement across stressors. HRV decreased significantly from rest for all stressors ( p  = 0.0003, p  = 0.0112, p  = 0.0027 for medical difficulty, interpersonal challenge, and equipment failure, respectively), but there was no statistically significant difference between mean change in HRV across stressors (one way ANOVA, F[2, 120] = 0.17, p  = 0.8452). Conclusions: Interpersonal challenge stressor was significantly associated with an increase in distress in EM residents during the simulated encounters as compared to the other stressors. While heart rate variability decreased from rest for each stressor as expected following stressor introduction, differing stressors did not produce a differential change.